Perlindungan Hukum bagi Investor dalam Era Transformasi Digital: Kajian Hukum Bisnis di Indonesia - Lim, Feili; Lie, Gunardi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of investment in Indonesia has grown rapidly, particularly with the emergence of digital instruments such as fintech, app-based capital markets, and crowdfunding. This situation presents both opportunities and legal risks for investors. This article examines how Indonesian business law responds to these developments, with a focus on legal protection for investors. The inestigation methodology applied is a normative juridical approach by reviewing investment-related legislation and analyzing relevant cases. The findings indicate that although a legal framework is already in place, practical implementation still reveals weaknesses, especially in terms of supervision and law enforcement. Therefore, it is necessary to strengthen regulations and enhance synergy among institutions to ensure legal certainty and investor protection.